Annual Plan (1974-75) Union Territory of Delhi - Planning Commission (Planning Commission, 1974)
Outlay and Expenditure-Summary, Programme-Wise Outlay and Expenditure, Scheme-Wise Proposed Outlay, Scheme-Wise Proposed Outlay, Agriculture Programmes, Cooperation Panchayats and Land Reforms, Irrigation and Power, Industry, Roads Transport and Tourism, Social Services.
Union Territory of Delhi, Planning Department